Supramolecular Rare Sugar. Issue 1 (April 2020) - Ishii, Tomohiko; Senoo, Tatsuya; Taguchi, Hiroaki; Sogo, Kouta; Huy, Bui Quoc; Taniguchi, Norito; Katsumoto, Syuichi; Nagayama, Natsumi; Sakane, Genta
Abstract: We introduce rare sugars including their derivatives and supramolecular rare sugars, that have been actively researched at Kagawa University, Japan. Although the rare sugars are special sugars which hardly exist in nature, we has succeeded in mass synthesis of the rare sugars by utilizing biological enzyme isomerization reaction. In addition, the rare sugars have various functions such as blood sugar level suppressing function, cancer cell growth suppressing function, and antibacterial action. In addition, since rare sugars have a large number of hydroxyl groups, they have a possibility for using as devices for expressing various functions by employing them as ligands of transition metal complexes. In recent years, it is successful that we have synthesized the suplamolecular rare sugars (SRSs) from the different types of rare sugars, that is not as simple mixtures but as single crystals having supralattice structure, that can be freely controlled optical rotation. It has been found that the crystal structures of these SRSs mostly follow the Wallach rule, but do not satisfy the Wallach rule especially in the case of D, L-psicose. Therefore, we have investigated the single crystal X-ray structural analyses of SRSs, obtaining the detailed crystal structure data, and analyzed the intermolecular interaction between their sugar molecules in the crystal by means of the DV-Xα molecular orbital calculation. According to our detailed analysis of the research, calculating the intermolecular interaction revealed that the stability of the intermolecular interaction in the crystal can not be explained only by following the simple Wallach rule. Specifically, for example in the case of D, L-psicose, the total energy in a crystal can be stabilized by aligning the polarization vectors of the molecules, and as a result, we have clarified that the SRSs crystal structure can be stabilized, even if it does not follow the simple Wallach rule.